Kontribusi Pendidikan Kewirausahaan dan Lingkungan Keluarga terhadap Niat Berwirausaha: Peran Mediasi Religiusitas - Solihin, Rici; Sobandi, Ade; Furqon, Chairul (Universitas Pendidikan Indonesia, 2023)
This study aims to determine how the impact of Entrepreneurship Education and the Family Environment on Entrepreneurial Intention, considering that account the mediating role of religiosity. Increasing Entrepreneurial Intention is an important factor in generating new entrepreneurs, notably in facing financial and social issues in global competition. Therefore, this study intends to dig deeper into what are the critical factors that can influence Entrepreneurial Intention. This study adopted a quantitative approach and involved 162 respondents from multiple educational and religious backgrounds. This research analysis adopts the Structural Equation Modeling (SEM) technique with the Partial Least Squares (PLS) approach. This research has important effects in the perspective of entrepreneurship education and policy development. It is hoped that the findings of this study can offer practical suggestions for educational institutions, families and the government in increasing Entrepreneurial Intention through the effective role of entrepreneurship education, a conducive family environment, and the growth of the religious dimension.